MATERI KEBAHASAAN DALAM BUKU PELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Lismiati Lismiati (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2014)
The aim of the study was to describe phoneme/spelling materials, materials of forms and kind of words, sentence materials, and paragraph/discourse material in the Indonesian language textbook at elementary school of Drokilo II. The collection of data is done by using writing method. The research data are aken from two Indonesian language textbook that are used at the fifth grade of elementary school, namely Bahasa Indonesia untuk Sekolah Dasar Kelas V” written by Umri Nuraini dan Indriyani and “Indahnya Bahasa dan Sastra Indonesia untuk SD/MI Kelas V” written by H. Suyatno. The research result show both books cantain grammar material that consists of phoneme/spelling, forms/kind of words, sentences, and paragraph/discourse. Both books are relevance can be seen from the conformity between the materials in both books and basic competence in the curriculum.